Dangerosité et pratique criminologique en milieu adulte - Dozois, Jean; Lalonde, Michèle; Poupart, Jean (Criminologie, 1984)
After a brief review of the criticism leveled at the definitions and use of dangerousness, this article examines how criminol-ogists work with it on a daily basis within the adult justice system.We first describe the important place it occupies in their practice, notably in their work of evaluating and treating the clientèle. Next we analyze the process by which criminologists effect the social reconstruction of their clients' dangerousness. To do this, we ascertain how criminologists categorize the clientèle as dangerous or not dangerous, and also show the influence of the practice on the process by which criminologists define dangerousness.